Assessment of awareness and knowledge regarding gluten, gluten-free diet, and celiac disease among university students - Mahitab Hanbazaza; Jood Bin Ghanem; Aziza Ishiq; Naylah Almoukhtar (International Journal of Food and Nutritional Health, 2026)
Lifelong adherence to a strict gluten-free diet is the only known treatment for celiac disease. This study aimed to assess the awareness and knowledge level of students at King Abdulaziz University in Saudi Arabia regarding gluten-free diet and celiac disease. A descriptive cross-sectional study was conducted among a convenience sample of 1136 bachelor's students from various academic fields, using a web-based questionnaire. Data collection included demographic characteristics, knowledge of gluten, gluten-free diet, and celiac disease, and their relationship. The majority of participants were females (94.2%) and aged between 18-20 years (46.83%). Findings indicated poor awareness of celiac disease, with 75.1% of students reporting they had never heard of celiac disease. In contrast, 75.4% of participants were familiar with a gluten-free diet. Approximately half of the participants (51.9%) showed poor knowledge of celiac disease, while only 25.8% had good knowledge. Regarding the gluten-free diet, 22.3% of participants exhibited moderate knowledge, while 36.8% had poor knowledge. Significant differences in knowledge about celiac disease and gluten-free diet were observed based on gender (P = 0.012 and 0.008, respectively) and academic field (P <0.001 for both). Regarding knowledge of the relationship between celiac disease and gluten-free diet, 47.2% of participants demonstrated moderate knowledge, with significant associations observed only with the academic field (P <0.001). The findings revealed a lack of knowledge about celiac disease and gluten-free diet among KAU students in Saudi Arabia. Developing and implementing nutritional education programs may enhance understanding of celiac disease and its association with a gluten-free diet.